2013
DOI: 10.1016/j.febslet.2013.06.049
|View full text |Cite
|
Sign up to set email alerts
|

NO/cGMP/PKG signaling pathway induces magnesium release mediated by mitoKATP channel opening in rat hippocampal neurons

Abstract: Edited by Peter Brzezinski

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Under physiological conditions, depolarization triggers an increase of [Mg 2+ ] i in sensory neurons 6 , while glutamate exposure induces a [Mg 2+ ] i surge in forebrain and hippocampal neurons 7,8 . More recently, it was shown that activation of a nitric oxide signaling pathway can also trigger an increase of [Mg 2+ ] i in hippocampal neurons 9 . Moreover, enhanced [Mg 2+ ] i can be expected with a reduction in the levels of ATP during periods of waking and hyperactivity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, depolarization triggers an increase of [Mg 2+ ] i in sensory neurons 6 , while glutamate exposure induces a [Mg 2+ ] i surge in forebrain and hippocampal neurons 7,8 . More recently, it was shown that activation of a nitric oxide signaling pathway can also trigger an increase of [Mg 2+ ] i in hippocampal neurons 9 . Moreover, enhanced [Mg 2+ ] i can be expected with a reduction in the levels of ATP during periods of waking and hyperactivity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicated that all animals in different treatment groups learned how to find the hidden platform after 4 days of training by memorizing the signs on surrounding walls. Based on other investigations, NO can produce cGMP through soluble guanylate cyclase, and afterward cGMP activates PKG in the neurons [9,24]. Besides, according to our behavioral and molecular ….. Aβ + KT…..…”
Section: Discussionmentioning
confidence: 64%
“…As the pathogenesis of AD has not yet been determined completely, we suggest PKG signaling pathway as the probable interfering mechanism in this disorder. Based on other investigations, NO can produce cGMP through soluble guanylate cyclase, and afterward cGMP activates PKG in the neurons [9,24]. The intracellular mechanism of PKG is not well understood yet, but the role of PKG in regulating ERK has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Brain slice preparations of cholinergic neurons of the basal forebrain of Wistar rats demonstrate that PKG alters the function of K + leak channels [ 47 ] and although the changes in K + channel function were explored with increasing pH, the effect of an environmental stressor, such as anoxia or hyperthermia, was never applied. For both the K + leak channels and K + pumps implicated as targets of PKG modulation [ 49 , 50 ], a change in either could alter the membrane potential of the bouton to alter neuronal excitability and firing capabilities. While PKG modulation appears to have a predominant effect on neuronal function during stress as seen with the drastic differences in Ca 2+ dynamics at higher temperatures, there is still a slight change in Ca 2+ dynamics at room temperature ( Fig 2C ).…”
Section: Discussionmentioning
confidence: 99%